Sandwich-structured nanohybrid paper based on controllable growth of nanostructured MnO2 on ionic liquid functionalized graphene paper as a flexible supercapacitor electrode. Issue 17 (7th April 2015) - Sun, Yimin; Fang, Zheng; Wang, Chenxu; Ariyawansha, K. R. Rakhitha Malinga; Zhou, Aijun; Duan, Hongwei
Abstract : A sandwich-structured flexible supercapacitor electrode has been developed by controllable template-free ultrasonic electrodepositing MnO2 nanonests on freestanding ionic liquid functionalized graphene paper. Abstract : A sandwich-structured flexible supercapacitor electrode has been developed based on MnO2 nanonest (MNN) modified ionic liquid (IL) functionalized graphene paper (GP), which is fabricated by functionalizing graphene nanosheets with an amine-terminated IL ( i.e., 1-(3-aminopropyl)-3-methylimidazolium bromide) to form freestanding IL functionalized GP (IL–GP), and then modifying IL–GP with a unique MNN structure via controllable template-free ultrasonic electrodeposition. The as-obtained MNN modified IL–GP (MNN/IL–GP) inherits the excellent pseudocapacity of the metal oxide, the high conductivity and electric double layer charging/discharging of IL–graphene composites, and therefore shows an enhanced supercapacitor performance. The maximum specific capacitance of 411 F g −1 can be achieved by chronopotentiometry at a current density of 1 A g −1 . Meanwhile, the MNN/IL–GP electrode exhibits excellent rate capability and cycling stability, its specific capacitance is maintained at 70% as the current densities increase from 1 to 20 A g −1 and 85% at a current density of 10 A g −1 after 10 000 cycles. More importantly, the MNN/IL–GP displays distinguished mechanical stability and flexibility for device packaging, although its thickness is merely 8 μm. These features collectively demonstrate the potential of MNN/IL–GP as a high-performance paper electrode for flexible and lightweight and highly efficient electrochemical capacitor applications.